Influence of Different Secondary Fermentation Yeasts on Aromatic Profiles of Sparkling wines - Iva Šikač; Ana Jeromel; Ivana Tomaz; Bernarda Kozina; Ana-Marija Jagatić Korenika (Glasnik Zaštite Bilja, 2022)
The production of sparkling wines occupies an increasing share of the total world wine production. During the last decade, there has been an increase in the production and consumption of sparkling wines in the Republic of Croatia. Secondary fermentation and maturation on yeast lees are key stages of the traditional production method, which affects the aromatic profile of sparkling wines. In the research on white sparkling wine produced from the varieties 'Manzoni' and 'Pinot noir', three different commercially available Saccharomyces sp. yeast in the initiation of secondary fermentation were used to analyze potential differences in the basic composition and aromatic profile of sparkling wines. The results of the gas chromatography (GC-MS) analysis clearly distinguish the aromatic compounds created by the use of different yeasts, which significantly influenced the differences in the aromatic profiles of the produced sparkling wines.